PENGARUH VARIASI SUHU DAN WAKTU PENGERINGAN PADA PEMBUATAN ENZIM PAPAIN DARI EKSTRAK DAUN PEPAYA - Muyassaroh; Nilna, Faidliyah Nilna Minah; Azizah, Wasiatul; Sabrina, Mala (jurnal ATMOSPHERE, 2021)
Papaya leaves have long been known as leaves that contain meat tenderizers. Papaya leaves can soften the meat because it contains papain which is one of the protease enzymes. In the fresh papaya leaves there is sap which contains 5.3% papain. Meat tenderizer in powder form is more practical and more durable. One of the papain enzyme powder drying methods that is considered appropriate to be applied in the ginger powder production process is the foam mat drying method. This study aims to examine the foam drying process on papain enzyme activity using tween 80 (foam agent) and maltodextrin as filler to help maintain foam consistency. The drying process was carried out by varying the drying temperature (50oC, 55oC, 60oC, 65oC, and 75oC) and drying time (2 hours, 3 hours, 4 hours, 5 hours and 6 hours). The results of the analysis showed that the highest enzyme activity reached 408.7 U/mL for drying at an operating temperature of 60oC with a time of 2 hours..